The Echoes of the Past: A Post-Traumatic Reading of Racial Injustice in James Baldwin’s Go Tell It on the Mountain - Newbehin A; Dr R. Anto Sindhuja (ILN Journal: Indian Literary Narratives, 2025)
Trauma is an encounter of the violent event, with its unexpectedness and horror. Traumatic disorders transpire when there is an interplay between the experience and memory along with their gender violence. The most destructive psychiatric disorder of all is post-traumatic stress disorder that provides a direct link between psyche and external violence. This paper explores the psychological impact of racial discrimination through a trauma-theoretical lens in James Baldwin’s Go Tell It on the Mountain. Focusing on the characters of Richard and Elizabeth, the study examines how post-traumatic stress disorder (PTSD) manifests as a result of systemic racism, personal loss, and generational trauma within the African American experience. Drawing on theories by Sigmund Freud and Cathy Caruth, the paper identifies symptoms of PTSD such as re-experiencing, avoidance, emotional numbing, and heightened arousal in the lives of Baldwin’s characters. Through close textual analysis, the study reveals how Baldwin portrays trauma not only as an individual psychological struggle but also as a collective historical burden that shapes identity and relationships. Despite enduring emotional suffering, both Richard and Elizabeth exhibit forms of resilience and resistance, underscoring Baldwin’s nuanced portrayal of survival amid oppression. This research contributes to trauma studies in literature by highlighting how Baldwin’s narrative reflects the enduring scars of racial injustice and the psychological complexities of Black life in America.